2019
DOI: 10.1515/applirev-2018-0114
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in language learning and teaching: Translingual practices and transcultural identities

Abstract: This introduction explores the four main themes of the papers in this special issue: 1) ‘language, languaging and translanguaging’ 2) ‘mobility and space’ 3) ‘transcultural identities’ and 4) ‘institutional and individual constraints on creativity’, and discusses how engagement with these themes helps the authors to move beyond traditional notions of linguistic creativity and creative pedagogy to formulate new ways of imagining creativity in language learning based on encouraging learners to make use of the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
1
12
0
2
Order By: Relevance
“…Against the immersed language learning or the monolingual pedagogy, translanguaging allows learners and teachers to leverage various linguistic, semiotic and translingual resources as an integrated system to complete certain tasks or achieve certain goals (Canagarajah, 2011; García and Li, 2014; Li, 2018; Yuzlu and Dkilitas, 2021). In other words, translanguaging as a pedagogical practice provides opportunities for learners to use their linguistic and non-linguistic repertoires in ways that may deepen their engagement and comprehension in the process of learning (Jones, 2020; Li, 2010; Vogel and García, 2017). It may also act as a glue strengthening the relationship between students and teachers (Vogel and García, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Against the immersed language learning or the monolingual pedagogy, translanguaging allows learners and teachers to leverage various linguistic, semiotic and translingual resources as an integrated system to complete certain tasks or achieve certain goals (Canagarajah, 2011; García and Li, 2014; Li, 2018; Yuzlu and Dkilitas, 2021). In other words, translanguaging as a pedagogical practice provides opportunities for learners to use their linguistic and non-linguistic repertoires in ways that may deepen their engagement and comprehension in the process of learning (Jones, 2020; Li, 2010; Vogel and García, 2017). It may also act as a glue strengthening the relationship between students and teachers (Vogel and García, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result revealed that there was a significant difference between the two conditions of online peer feedback, with the translanguaging condition being more conducive to L2 writing performance. Such a result may be due to the fact that translanguaging involves the deployment of all possible linguistic and non-linguistic repertoires, leading to better meaning negotiation and idea exchange (Jones, 2020;Li, 2010;Vogel and García, 2017). Specifically, L1 use can be cognitively less demanding which enabled learners to produce more comments on content and offer more specific linguistic feedback (Cheng and Zhang, 2021;Yu, 2016).…”
Section: Effectiveness Of Translanguaging In Online Peer Feedback On ...mentioning
confidence: 99%
“…en diferentes géneros discursivos, sino también el valor de estos repertorios multimodales en la conformación de estilos verbales que sirvan para distinguir y delimitar identidades individuales y también grupales (Eckert, 2003). Aunque sin afán de plantear generalizaciones, consideramos que estas reflexiones pueden orientar futuros estudios sobre los vínculos entre la creatividad lingüística (Jones, 2019) que emerge en la escritura en pantallas y las prácticas de escritura multimodal en los géneros discursivos escolares.…”
Section: El Análisis: Algunos Criteriosunclassified
“…The authors use the term transcultural communication to describe the movement of texts and images across cultural and linguistic boundaries. During this transcultural communication, it is natural for translanguaging to occur, this term being understood as the dynamic use of the full linguistic repertory in interaction (Baker & Sangiamchit, 2019;Jones, 2019;Vallejo & Dooly, 2020). We hold that the notion of transcultural communication provides the ideal framework for analysing online interaction that jumps back and forth across linguistic and cultural boundaries.…”
Section: Transcultural Communication and Translanguaging In A Fandommentioning
confidence: 99%
“…The new literacy studies is a theoretical framework frequently used in fan studies focused on language learning (Aliagas, 2017;Gee & Hayes, 2012;Shafirova et al, 2020;Vazquez-Calvo, 2018;Vazquez-Calvo et al, 2020;Zhang & Cassany, 2016, 2019. This framework describes reading and writing as social practices engraved in the coordinates of people's daily routines.…”
Section: The New Literacy Studies and Transcultural Literacies In A Fmentioning
confidence: 99%